Defining an effective approach to blended learning in higher education : A systematic review - McCarthy, Shaun; Palmer, Edward (Australasian Journal of Educational Technology, 2023)
Blended learning has enjoyed wide acceptance as a teaching and learning approach in higher education, but its use and understanding commonly fail to extend across all levels of blending. At the institutional level, challenges still exist in aligning a blended learning approach with core university priorities. Often, there is a focus on the provisions of technology tools and associated training; however, there is less emphasis on the development of frameworks that support an institutional-level approach to blended teaching and learning and ways that these can be effectively measured. This paper analyses previous work undertaken in the field of blended learning and looks to build on the literature by defining an effective approach to adoption using conceptual clarity, blended frameworks and institutional-level implementation of blended learning as a framework to describe effective use within higher education. [Author abstract]